In-Service Training Programs: Iraqi Secondary School EFL Teachers‟ Motivation - Mohammed Mustafa, Saad; Abdul Malik Mohamed Ismail, Shaik (International Journal of Psychosocial Rehabilitation, 2020)
Most research studies on EFL and ESL teaching and learning (e.g., Mahmood, 2016) have shown that a well-organized in-service training program would boost EFL secondary school teachers’ competence to effectually realize classroom events and activities and encourage the educational institutions to recognize their purposes and eventually improve the teaching process. Furthermore, current studies have confirmed that Iraqi EFL teachers should be fully enthused and motivated to attend such programs and consider their application. O’Malley's (2010) and Koran’s (2015) studies revealed that the lack of job safety due to the insecure circumstances in Iraq may influence teachers’ motivation to attend the in-service training programs. This in return may affect the purposes of the programs and may undesirably affect Iraqi secondary school EFL teachers’ performance.Thus, this paper is intended to collect Iraqi EFL teachers' views and perceptions of issues related to their motivation to join the in-service training program and apply its outcomes in their teaching careers. In other words, it focuses on illuminating the influence of the teachers’ motivation on the effectiveness of the training program. Ninety Iraqi EFL secondary school teachers from Baghdad, Al-Risafa part, volunteered to take part in the questionnaire and to answer its 20 items.Based on the Likert scale, the applicants avow that motivation is a crucial factor in building the program and add that when teachers are motivated, they will definitely accomplish more in teaching classes. Further, to consolidate teachers' motivation, the training program must develop building teachers' teaching confidence; teachers' received salaries should be respected, and training should be emphasized in in-service programs to increase teachers' self-consciousness of teaching training.